Prevalence of gastrointestinal nematodes in Mukota pigs in a communal area of Zimbabwe - M. C. Marufu; P. Chanayiwa; M. Chimonyo; E. Bhebhe (African Journal of Pig Farming, 2015)
A one year monitoring study was conducted between November 2005 and October 2006 to determine the prevalence of gastrointestinal nematodes in indigenous Mukota pigs in Hama-Mavhaire communal area of Chirumhanzu District, Zimbabwe. Faecal samples from a total of 143 randomly selected pigs of both sexes and different ages (< 5 months, 5 -12 months and > 12 months) from 10 villages were collected from the rectum for identification and quantification of nematode eggs. Of the 143 pigs, 58.7% were positive for gastrointestinal (GI) nematodes, 17.5% having mixed infections. Four parasite species were identified; Oesophagostomum species (54.6%) being the most prevalent followed by Strongyloides ransomi (14%), Ascaris species (7%) and Trichuris suis (4.2%). Month had an effect on the prevalence and mean egg counts of the four GI nematode species. However, pig class and the interaction between pig class and month did not have an effect on the prevalence and mean egg counts of the GI nematode species. The present work indicates that parasite prevalence in local indigenous pigs in the communal areas is moderate. Further examinations are needed to determine the pathological importance and impact of parasitic infestations on indigenous pigs in the communal area.